The Science Fiction of the Past, the Reality of the Present – Smart Cities - KAUR, Komalpreet; BUȘA, Ioana Isabel; CUC, Lavinia Denisa (Studia Universitatis Babeș-Bolyai Negotia, 2024)
The concept of smart cities has gained recognition in the last few years because of the increasing urban population coupled with rise in the number of urban problems. Smart cities – usage of information and communication technology (ICT) to enhance the standard of living, thereby, represents a digital solution for the urban communities that aims for economic growth and sustainability. The present paper offers an overview of this innovative concept. Smart Mobility, Smart Economy, Smart People, Smart Environment, Smart Living and Smart Governance are the six pillars of a smart city. However, the article puts an emphasis on smart governance, while providing a brief description of all the other dimensions. By highlighting some of the benefits and challenges that smart governance offers to urban citizens, it presents the significance of collaboration between different stakeholders including citizens, public institutions and government officials. In conclusion, the study argues smart governance is essential for promoting good governance practices but there is a need to consider the other factors such as social inclusion and basic human rights while adopting this new method in decision-making process. Article history: Received: September 22, 2023; Reviewed: December 10, 2023; Accepted: February 27, 2024; Available online: March 29, 2024. JEL Classification: O18, Q56, R59.